Variable-Frequency and Phase-Shift With Synchronous Rectification Advance On-Time Hybrid Control of LLC Resonant Converter for Electric Vehicles Charger - Lin, Jing-Yuan; Yueh, Hsuan-Yu; Lin, Yi-Feng; Liu, Pin-Hsien (IEEE journal of emerging and selected topics in industrial electronics (Print), 2023)
The LLC resonant converter has been widely used in the power supply industry, such as server power, TV power, and adapter, because this converter can realize the zero-voltage switching (ZVS) at the power mosfet s of the primary side. Thus, the switch losses can be decreased, and the conversion efficiency can also be improved. The electric vehicle (EV) charger has been recently widely used in research and development. However, designing LLC resonant converters for the wide battery voltage range is difficult because this converter is usually utilized in pulse-frequency modulation (PFM) to regulate the output voltage. This converter will also be limited to the low operating frequency range for the high conversion efficiency due to the switching frequency. By contrast, the phase-shift modulation (PSM) control for the wide output voltage range has been used at LLC resonant converters. However, the ZVS will be lost due to the lagging leg of the LLC resonant converter when the phase-shift angle is remarkably excessive. The burst-mode control has also been proposed for the converter to regulate the output voltage and maintain high conversion efficiency at light-load conditions. Therefore, this article utilized the combination of PFM, PSM, and burst-mode control for the LLC resonant converter operating at the wide output voltage range for EV charge applications. Furthermore, this article proposed a synchronous rectification advance on-time control for PFM control, which can help address the ZVS at the lagging leg when the phase-shift angle is excessive. Detailed analysis and design of this control method are also described. The performance evaluation of the proposed LLC resonant converter with hybrid control was finally realized under the following conditions: 3.75 kW, dc input voltage of 400 V DC , dc output voltage of 75-475 V DC , and maximum conversion efficiency around 97%.